The Difficult Airway Trolley: A Narrative Review and Practical Guide - Martin F. Bjurström; Mikael Bodelsson; Louise W. Sturesson (Anesthesiology Research and Practice)
Death and severe morbidity attributable to anesthesia are commonly associated with failed difficult airway management. When an airway emergency develops, immediate access to difficult airway equipment is critical for implementation of rescue strategies. Previously, national expert consensus guidelines have provided only limited guidance for the design and setup of a difficult airway trolley. The overarching aim of the current work was to create a dedicated difficult airway trolley (for patients>12 years old) for use in anesthesia theatres, intensive care units, and emergency departments. A systematic literature search was performed, using the PubMed, Embase, and Google Scholar search engines. Based on evidence presented in 11 national or international guidelines, and peer-reviewed journals, we present and outline a difficult airway trolley organized to accommodate sequential progression through a four-step difficult airway algorithm. The contents of the top four drawers correspond to specific steps in the airway algorithm (A = intubation, B = oxygenation via a supraglottic airway device, C = facemask ventilation, and D = emergency invasive airway access). Additionally, specialized airway equipment may be included in the fifth drawer of the proposed difficult airway trolley, thus enabling widespread use. A logically designed, guideline-based difficult airway trolley is a vital resource for any clinician involved in airway management and may aid the adherence to difficult airway algorithms during evolving airway emergencies. Future research examining the availability of rescue airway devices in various clinical settings, and simulation studies comparing different types of difficult airway trolleys, are encouraged.